Analysis of the relationship between emotional quotient and physical activities on fundamental motor skills of elementary school - Dese, Dennys Christovel; Wibowo, Cahyo (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
The significance of emotional quotients (EQ) and physical activities in developing fundamental motor skills in elementary school students was the primary reason for this study. This study analyzes the relationship between EQ and physical activities with fundamental motor skills among elementary school students aged 7-9. The research method employed observational analytics with a cross-sectional approach. The study population consisted of students from Kurma Islamic Elementary School in Salatiga, with a sample of 80 students aged 7-9. Data were collected through questionnaires (EQ), PAQ-C, and performance-based motor skills assessment rubric. Data analysis was conducted using Pearson correlation and linear regression tests. The results showed a significant relationship between EQ and fundamental motor skills. Additionally, there was a significant relationship between physical activities and fundamental motor skills. Regression analysis indicated that EQ and physical activities significantly influenced fundamental motor skills simultaneously. This study reveals that both EQ and physical activities significantly impact fundamental motor skills in elementary school students. The implications of the findings underscore the significance of integrating holistic education programs, incorporating EQ development, and promoting physical activity to support overall motor development and well-being in children.